Building construction - Mckay, J.K.; McKay, W.B. (New Delhi Pearson Education, 2013)
A well-established series of reference books covering various aspects of building construction. Volumes I, II and III are concerned essentially with the principles and sound methods of construction chiefly traditional in character. Volume IV describes more advanced building techniques with the latest systems well illustrated.
Keywords: BRICKWALLS,FOUNDATION;MASONRYWALLS;TIMBER,FLOORSANDROOFS,DOORS,WINDOS,STAIRS;ROOFCOVERINGS;PLUMBING;MILDSTEELSECTIONS,BOLTSANDRIVETS; BUILDING CONSTRUCTION (BT-CON)